Incidental Finding of Thyroid Tuberculosis by Operation for Graves’ Disease: A Rare Case Presentation - Zineb El Azime; Samira Handa; Ghita Bourkadi; Hayat Aynaou; Houda Salhi; Hanan El Ouahabi (Case Reports in Endocrinology)
Thyroid tuberculosis is a rare form of extrapulmonary tuberculosis, even in endemic countries such as Morocco; its precise incidence is not well-defined. The clinical presentation of thyroid tuberculosis can vary, often being asymptomatic. Consequently, the diagnosis may be overlooked or delayed. Intriguingly, thyroid tuberculosis can manifest alongside thyrotoxicosis due to Graves’ disease, an exceptional association. This article reports a distinctive case of thyroid tuberculosis coexisting with Graves’ disease, one of the autoimmune thyroid diseases. A 33-year-old female presented symptoms consistent with hyperthyroidism and bilateral exophthalmos. She was subsequently diagnosed with Graves’ disease. Despite initially managed medically, recurrences of the disease led to definitive treatment by total thyroidectomy. Histopathological examination revealed concurrent presence of thyroid tuberculosis.